The many faces of the Seyfert galaxy NGC 5643 - Macedo, Pedro Henrique Cezar Remião de (2022)
We carried out a detailed analysis of the central 350 pc of the galaxy NGC 5643. We aimed to probe the conditions and mechanisms behind the gas emission. For that, high spatial resolution optical and near-infrared integral field spectroscopy data were analyzed. Detailed studies in the nearby Universe, as the current, provide further evidence of how AGN-driven phenomena impact the gas of galaxies.